Coordination Frameworks based on 3, 5‐Bis(imidazole‐1‐yl)pyridine and Aromatic Dicarboxylate Ligands: Synthesis, Crystal Structures, and Photoluminescent Properties1. Issue 1 (23rd August 2013) - Xu, Jiakun; Sun, Xiaochun; Yang, Lirong; Yan, Xincheng; Bi, Caifeng; Sun, Mi
Abstract Three metal coordination polymers [Zn(bdc)(L)(H2O)]n (1), [Co(pta)(L)(H2O)2]n (2), and [Cd(tda)(L)(H2O)]n (3) [H2bdc = 1, 2‐benzene dicarboxylate acid, H2pta = terephthalic acid, H2tda = 2, 5‐thiophenedicarboxylic acid, L = 3, 5‐bis(imidazole‐1‐yl)pyridine] were synthesized and structurally characterized by IR spectroscopy, elemental analysis, X‐ray powder diffraction, and X‐ray single crystal diffraction. Complex 1 shows a three‐dimensional (3D) structure with cco topology with the symbol 65·8, whereas complex 2 features a 3D structure with cds topology with the symbol 65·8. Complex 3 has a 2D network constructed by the cadmium atoms bridged through the ligands tda and L. Their X‐ray powder diffraction patterns were compared with the simulated ones. Moreover, their luminescent properties were investigated in the solid state at room temperature, and the thermogravimetric analyses were carried out to study the thermal stability of the 3D networks.